Demonstration of a mixed-methods illuminative evaluation: the case of a sports and exercise academic program - Bryan Nozaleda; Hans Freyzer Arao; Maricel Dayag-Tungpalan; Jasmin Saquing; Chita Ramos; Daniel Casauay (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: In sports and exercise science education, ensuring that curricular components translate into practical skills is particularly critical. Higher education programs often struggle to align their instructional design with the actual learning experiences of students.